Disparities of Trastuzumab Use in Resource‐Limited or Resource‐Abundant Regions and Its Survival Benefit on HER2 Positive Breast Cancer: A Real‐World Study from China. (10th August 2017) - Li, Jianbin; Wang, Shusen; Wang, Yongsheng; Wang, Xiaojia; Wang, Haibo; Feng, Jifeng; Zhang, Qingyuan; Sun, Tao; Ouyang, Quchang; Yin, Yongmei; Liu, Yinhua; Geng, Cuizhi; et al.
Abstract: Background: Trastuzumab is a key component of therapy for human epidermal growth receptor 2 (HER2) positive breast cancer. Because real‐world data are lacking, the present research was conducted to evaluate the actual use of and the effectiveness of trastuzumab in the real world in China. Methods: Inpatients with HER2 positive invasive breast cancer from 13 hospitals in Eastern China (2010–2015, n  = 1, 139) were included in this study. We aimed to assess the actual use of trastuzumab and to evaluate potential efficacy from trastuzumab in real‐world research. Results: Of 1, 017 patients with early stage breast cancer (EBC), 40.5% (412/1, 017) received trastuzumab therapy. Patients with EBC in resource‐abundant regions (gross domestic product per capita >$15, 000 and trastuzumab included in Medicare) are more likely to receive trastuzumab than those in resource‐limited regions (37.3% vs. 13.0%, p  < .05). After metastasis, 50.8% (366/720) patients received trastuzumab as their first‐line therapy. More than 10% of patients with metastatic breast cancer (MBC) continued trastuzumab therapy after twice progression in resource‐abundant regions, whereas more than 40% of patients never received any trastuzumab therapy during the whole course of therapy in resource‐limited regions. Overall, the improvement in survival for trastuzumab versus non‐trastuzumab was substantial in EBC (hazard ratio [HR] = 0.609, 95% confidence interval [CI]: 0.505–0.744) and in MBC (HR = 0.541, 95% CI: 0.418–0.606). This association was greater for patients with MBC who had never received trastuzumab (HR = 0.493, 95% CI: 0.372–0.576) than for those who had received adequate trastuzumab therapy in EBC stage (HR = 0.878, 95% CI: 0.506–1.431). Conclusion: This study showed great disparities in trastuzumab use in different regions and different treatment stages. Both EBC and MBC patients can benefit from trastuzumab, as the survival data show; however, when trastuzumab is adequate in the early stage, a further trastuzumab‐based therapy in first‐line treatment of MBC will be ineffective, especially for those with short disease‐free survival, and a second line of anti‐HER2 therapy will be recommended. (Research number: CSCO‐BC RWS 15001). Abstract : The study of disparities in trastuzumab use has been complicated by the lack of population‐based cohorts. Real‐world research is lacking. This study used real‐world data from a multicenter study in China to explore disparities in trastuzumab use and to investigate the survival effects of trastuzumab on early stage and metastatic breast cancer.